1999
DOI: 10.1063/1.873242
|View full text |Cite
|
Sign up to set email alerts
|

Particle acceleration in relativistic laser channels

Abstract: Energy spectra of ions and fast electrons accelerated by a channeling laser pulse in near-critical plasma are studied using three-dimensional (3D) Particle-In-Cell simulations. The realistic 3D geometry of the simulations allows us to obtain not only the shape of the spectra, but also the absolute numbers of accelerated particles. It is shown that ions are accelerated by a collisionless radial expansion of the channel and have nonthermal energy spectra. The electron energy spectra instead are Boltzmann-like. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
491
3
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 639 publications
(522 citation statements)
references
References 29 publications
26
491
3
2
Order By: Relevance
“…Relativistic LPIs in low-density plasmas have a notable ability to produce high-energy electrons through several known mechanisms such as wake-field [3][4][5] and direct laser accelerations [6].…”
mentioning
confidence: 99%
“…Relativistic LPIs in low-density plasmas have a notable ability to produce high-energy electrons through several known mechanisms such as wake-field [3][4][5] and direct laser accelerations [6].…”
mentioning
confidence: 99%
“…Electrons injected at an angle with respect to the direction of propagation of the laser pulse were accelerated to MeV energies. Direct laser acceleration of electrons has been studied extensively and electron energies are predicted to be in the range of GeV energies (Esarey et al 1995;Pukhov et al 1999;Eloy et al 2007). In this paper, we also discuss direct laser acceleration of particles from a photon mirror (Eloy et al 2007;Mendonça et al 2007), and consider the radiation generation as the electrons are reflected from the photon mirror.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the trapped electrons that undergo betatron oscillations in the polarization plane of the laser will see an additional electric field from the laser. This transverse electric field of the laser, when in resonance with the betatron motion of the electrons [18][19], will in turn increase the transverse momentum of the trapped electrons. The resonance condition is achieved when a harmonic, N, of the betatron frequency, ω β , is on average [21] equal to the downshifted laser frequency (1-v || /v Φ )ω 0 witnessed by the trapped electrons; here v || is the longitudinal velocity of the electrons, v Φ is the phase velocity of the laser, and ω 0 is the laser frequency.…”
Section: Ionization-injected Lwfa In the Presence Of Dlamentioning
confidence: 99%
“…Recent simulations of LWFAs [17] have shown that in addition to wakefield acceleration, LWFAs can transfer energy from the laser to the electrons through a process known as DLA [18][19], which occurs when there is a considerable overlap between the trapped accelerated electrons and the laser field. Not only can this physical process enhance the final energy of the accelerated electrons and their betatron radiation [20], but it can also generate microbunched, attosecond electron beams before dephasing occurs.…”
Section: Ionization-injected Lwfa In the Presence Of Dlamentioning
confidence: 99%